RETRACTED ARTICLE: Silencing hsa_circ_PVT1 (circPVT1) suppresses the growth and metastasis of glioblastoma multiforme cells by up-regulation of miR-199a-5p. Issue 1 (1st January 2020) - Chi, Guonan; Yang, Fuwei; Xu, Donghui; Liu, Weiming
Abstract: We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Guonan Chi, Fuwei Yang, Donghui Xu & Weiming Liu (2020) Silencing hsa_circ_PVT1 (circPVT1) suppresses the growth and metastasis of glioblastoma multiforme cells by up-regulation of miR-199a-5p. Artificial Cells, Nanomedicine, and Biotechnology, 48:1, 188–196, DOI: 10.1080/21691401.2019.1699825 Since publication, concerns have been raised about the integrity of the data in the article. We reached out to the authors requesting that they supply information that would confirm the article's integrity. The authors provided several files in response to our queries, but they were unable to provide the original data in a format which satisfies our requirements to confirm the authenticity of some types of data. In particular, they were unable to provide full western blots, where the molecular weight markers are indicated. In addition, the authors did not have a record of the full blot, before cutting it into strips. When checking their data the authors also confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.